2006
DOI: 10.1529/biophysj.105.076950
|View full text |Cite
|
Sign up to set email alerts
|

Troponin T Modulates Sarcomere Length-Dependent Recruitment of Cross-Bridges in Cardiac Muscle

Abstract: The heterogenic nature of troponin T (TnT) isoforms in fast skeletal and cardiac muscle suggests important functional differences. Dynamic features of rat cardiac TnT (cTnT) and rat fast skeletal TnT (fsTnT) reconstituted cardiac muscle preparations were captured by fitting the force response of small amplitude (0.5%) muscle length changes to the recruitment-distortion model. The recruitment of force-bearing cross-bridges (XBs) by increases in muscle length was favored by cTnT. The recruitment magnitude was ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
165
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(173 citation statements)
references
References 42 publications
8
165
0
Order By: Relevance
“…This is consistent with the known effects of troponin T isoforms on muscle fiber force output in both insects and mammals (Chandra et al, 2006;MacFarland et al, 2002;Marden et al, 2001;Marden et al, 1999;Nassar et al, 2005), which presumably affect the rate of ATP consumption (Greaser et al, 1988). How variation in troponin T alternative splicing relates to mammalian muscle energetics in vivo is unknown.…”
Section: Introductionsupporting
confidence: 79%
“…This is consistent with the known effects of troponin T isoforms on muscle fiber force output in both insects and mammals (Chandra et al, 2006;MacFarland et al, 2002;Marden et al, 2001;Marden et al, 1999;Nassar et al, 2005), which presumably affect the rate of ATP consumption (Greaser et al, 1988). How variation in troponin T alternative splicing relates to mammalian muscle energetics in vivo is unknown.…”
Section: Introductionsupporting
confidence: 79%
“…There is nearly as strong a correlation between the summed relative abundance of the same two transcripts and the power output of intact muscle (Figure 3d). Experiments in other animals have repeatedly shown that manipulation of Tnt genes and/or protein isoforms affects muscle calcium sensitivity and contractile performance (Ogut et al, 1999;Gomes et al, 2002Gomes et al, , 2004MacFarland et al, 2002;Nassar et al, 2005;Brotto et al, 2006;Chandra et al, 2006), and single amino-acid replacement mutations in human Tnt also have these effects (Hernandez et al, 2005).…”
Section: As and The Generation Of Plastic Organism-level Phenotypesmentioning
confidence: 99%
“…In all animal species examined to date, Tnt undergoes alternative splicing (AS) to form multiple protein isoforms that differ in their amino acid sequence and function. Experiments with vertebrate striated muscle have consistently shown that manipulation of Tnt isoform content affects muscle calcium sensitivity and contractile performance (Ogut et al, 1999;Gomes et al, 2002;MacFarland et al, 2002;Gomes et al, 2004;Nassar et al, 2005;Brotto et al, 2006;Chandra et al, 2006). Single amino acid replacement mutations in human Tnt have similar effects (Hernandez et al, 2005).…”
Section: Introductionmentioning
confidence: 99%